U.S. Marines by the numbers - Raum, Elizabeth (North Mankato, Minnesota Capstone Press, a Capstone imprint, 2014)
"Describes aspects of the U.S. Marines using numbers, stats, and infographics"--
The world around us
Includes bibliographical references (page 31) and index
Grades 4 to 6
1 2 13 15
Keywords: United States -- Marine Corps -- Juvenile literature